2014
DOI: 10.1017/s0031182013002242
|View full text |Cite
|
Sign up to set email alerts
|

Is the tapeworm able to affect tissue Pb-concentrations in white rat?

Abstract: The effect of gastrointestinal helminths on Pb accumulation in the host body is ambiguous. A laboratory experiment with Rattus norvegicus/Hymenolepis diminuta model was conducted to determine Pb toxicokinetics in a terrestrial host-parasite system. The ET-AAS or ICP-OES techniques were used to determine Pb concentrations (CPb) in both tapeworms and host tissues (kidney, liver, bone, testes, muscle and intestinal wall). Concerning the entire host-parasite system, the highest CPb were detected in H. diminuta. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Some field studies followed and confirmed the higher uptake and bioconcentration of lead inside the parasite tissues in this host–parasite system (Sures et al , 2003; Al-Quraishy et al , 2014). Čadková et al (2014) also studied H. diminuta under laboratory conditions and confirmed a higher uptake of lead by this parasite. Although this parasite is well known to bioaccumulate lead in its tissues, information about the exact Pb localization along the tapeworm's strobila is lacking.…”
Section: Introductionmentioning
confidence: 79%
“…Some field studies followed and confirmed the higher uptake and bioconcentration of lead inside the parasite tissues in this host–parasite system (Sures et al , 2003; Al-Quraishy et al , 2014). Čadková et al (2014) also studied H. diminuta under laboratory conditions and confirmed a higher uptake of lead by this parasite. Although this parasite is well known to bioaccumulate lead in its tissues, information about the exact Pb localization along the tapeworm's strobila is lacking.…”
Section: Introductionmentioning
confidence: 79%
“…This analysis provided useful information regarding the molecular mechanisms behind host- Echinococcus interactions and Echinococcus biology. Comparative analyses of non-taeniid cestodes have been strikingly neglected, even though non-taeniid tapeworms (predominantly H. diminuta ) are widely used in experimental cestodology (Arai, 1980 ; Evans, 1980 ; McKay, 2006 , 2010 ; Johnston et al, 2009 , 2010 ; Melon et al, 2010 ; Shi et al, 2011 ; Bártíková et al, 2012 ; Graepel et al, 2013 ; Hernandez et al, 2013 ; Cadková et al, 2014 ; Harnett, 2014 ; Kosik-Bogacka et al, 2014 ; Shostak, 2014 ; Mansur et al, 2015 ; Reyes et al, 2015 ; Woolsey et al, 2015 ; Zawistowska-Deniziak et al, 2017 ). In the present study, we identified both stage-specific and common proteins of H. diminuta adults and cysticercoids, which helps not only to understand specific adaptations to parasitism and invasion, but may also provide the data necessary for planning experiments related to new drug targets, vaccines, or diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that parasites accumulate heavy metals much faster than their host, but a maximum is reached approximately after 4 weeks. Therefore, the bioaccumulation factor would tend to be smaller in chronic exposure situations (Oyoo-Okoth et al , 2012; Čadková et al , 2014). Additionally, methodological differences in tissue digestion could explain the results between different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Jankovská et al (2010b) found significant differences between parasitized and non-parasitized animals in an experimental study of lead accumulation in a sheep–cestode system ( Moniezia expansa/Ovis aries ). According to Čadková et al (2014), the toxicokinetics in a host body depends on the lead concentration to which it is exposed. However, and consistent with our results, for similar lead exposure levels no significant differences were found in lead concentration between parasitized and non-parasitized animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation